Living with Heart Failure during the COVID-19 Pandemic: An Interpretative Phenomenological Analysis. (September 2021) - Trenta, Alessia Martina; Ausili, Davide; Caruso, Rosario; Arrigoni, Cristina; Moro, Massimo; Nania, Tiziana; Vellone, Ercole; Dellafiore, Federica
This study aimed to explore lived experience of patients with heart failure (HF) during the COVID-19 pandemic. A qualitative study was conducted using an interpretative phenomenological analysis (IPA). Data collection performed in March-May 2020, using in-depth, semi-structured interviews on a purposive sample. Data were analyzed according to the IPA methodology, and triangulation, bracketing, journaling, and member checking were used to assure rigor. 14 patients with HF were enrolled, and three main themes described their lived experience during the COVID-19 pandemic: Vulnerability, Hanging in the balance, and Coping strategies. These people felt particularly vulnerable to the novel virus and experienced uncertainty due to hospital organization changes. Because of this, they felt like they were hanging in the balance, experiencing various negative feelings. Nevertheless, they managed to deal with this challenging situation by implementing some peculiar coping strategies. The COVID-19 represents a significant challenge for patients with HF, impacting significantly on their lives.